The Development of Interactive Learning Media Based on PBL Learning Models on Theme 9 Sub-theme 3 for Fifth Grade Elementary ASchool - Suwito, Wulan Endah Citra; Reffiane, Fine; Sary, Ryky Mandar (Universitas Pendidikan Ganesha, 2021)
The background that drives this research is that teachers are less than optimal in using instructional media in the learning process. Lack of use of learning media results in less active and passive student activities, so that students' understanding of the material is still lacking. This research aims to produce a product in the form of interactive learning media based on the PBL learning model that is valid and suitable for use in theme 9 sub-themes 3 for grade V SD. This type of research and development uses the ADDIE model. The data collection instrument in this study used a questionnaire. The method of data analysis in this research and development was carried out by using qualitative descriptive analysis techniques and quantitative descriptive analysis. Media experts and material experts validated that interactive learning media products developed were validated, showing the percentage of 84.89% and 82.67% were categorized as